Unforeseen plant phenotypic diversity in a dry and grazed world - Gross, Nicolas; Maestre, Fernando Tomás; Liancourt, Pierre; Berdugo, Miguel; Martin, Raphaël; Gozalo, Beatriz; Ochoa, Victoria; Delgado-Baquerizo, Manuel; Maire, Vincent; Ferrante, Daniela; Oliva, Gabriel Esteban; Le Bagousse-Pinguet, Yoann (Springer Nature, 2024)
Earth harbours an extraordinary plant phenotypic diversity1 that is at risk from ongoing global changes2,3. However, it remains unknown how increasing aridity and livestock grazing pressure—two major drivers of global change4–6—shape the trait covariation that underlies plant phenotypic diversity1,7. Here we assessed how covariation among 20 chemical and morphological traits responds to aridity and grazing pressure within global drylands. Our analysis involved 133,769 trait measurements spanning 1,347 observations of 301 perennial plant species surveyed across 326 plots from 6 continents. Crossing an aridity threshold of approximately 0.7 (close to the transition between semi-arid and arid zones) led to an unexpected 88% increase in trait diversity. This threshold appeared in the presence of grazers, and moved toward lower aridity levels with increasing grazing pressure. Moreover, 57% of observed trait diversity occurred only in the most arid and grazed drylands, highlighting the phenotypic uniqueness of these extreme environments. Our work indicates that drylands act as a global reservoir of plant phenotypic diversity and challenge the pervasive view that harsh environmental conditions reduce plant trait diversity8–10. They also highlight that many alternative strategies may enable plants to cope with increases in environmental stress induced by climate change and land-use intensification.